Development of a SNP-STRs multiplex for forensic identification. (December 2015) - Wang, L.; He, W.; Mao, J.; Wang, H.; Jin, B.; Luo, H.B.; Liang, W.B.; Zhang, L.
Abstract: The short tandem repeat (STR) and single nucleotide polymorphisms (SNP) are widely distributed in human genomes. SNP-STR, a compound genetic marker combining a STR locus with tightly linked SNPs, is more informative than any single polymorphism. The amplification refractory mutation system (ARMS) can allow DNA sample with specific base (e.g., SNP) amplify successfully, which avoids the common PCR bias in the analyses of mixtures. This study aims at enriching the rs25768-D5S818 (D5S818, from U.S. Core Loci) primers obtained in the previous study to develop a forensic SNP-STRs multiplex. Two SNP-STRs (rs2246512-D10S1248 and rs9531308-D13S317) were screened from the UCSC genome browser. Two forward SNP allele-specific primers labelled with different fluorescent dyes for each SNP-STR marker were designed with the ARMS, and a common reverse primer was designed near the 3′ region of STR. The amplicons of the three SNP-STRs were profiled via Genetic Analyzer ABI 3130. The sensitivity and specificity of the multiplex were confirmed by using the standard DNA (9947A). The SNP-STR genotype of minor component (0.05 ng) in the artificial extremely unbalanced two DNA mixture (ratio 1:40) was detected.